Analysis of Cannabinoids in Oil - Janis Vella Szijj; Lovely L. Gallo; Paul I. Buhagiar; Karolina Szyrner; Nicolette Sammut Bartolo; Simone Ronsisvalle; Anthony Serracino Inglott; Lilian M. Azzopardi (Integrative Medicine Reports)
Introduction: Cannabinoids are bioactive molecules found abundantly in the cannabis plant, with two major cannabinoids being Δ-9-tetrahydrocannabinol (THC) and cannabidiol. Method: The study was divided into three phases: (1) systematic literature search on the analysis of cannabinoids in oils, (2) development and validation of a rapid and efficient high-performance liquid chromatography (HPLC)-ultraviolet (UV) method for the determination of THC in medium-chain triglyceride (MCT) oil, and (iii) green assessment of methods for the determination of cannabinoids in oil. Results: Articles identified describe the analysis of cannabinoids in olive oil and hemp oil. Regarding the developed and validated method for analysis of THC in MCT oil, separation was achieved using an ACE C18-AR (250 × 4.6 mm; 5 µm) column with acetonitrile and 0.5% acetic acid (70:30, v/v) as the mobile phase at a flow rate of 2 mL/min. The analysis was conducted in isocratic mode with UV detection set at 220 nm. Injection volume was 10 µL. The method was validated in the linear range of 0.03125–0.5%. The method developed in this study was found to have equivalent greenness to other HPLC-UV methods reported in the literature. Discussion: The method has acceptable accuracy, precision, and stability, is relatively green, and can be successfully applied to determine concentrations of THC in commercially available cannabinoid-containing oils where the allowed limit of THC is 0.2–0.3%.